Diagnosis of toxoplasmosis and typing of Toxoplasma gondii - Liu, Quan (Parasit Vectors, 2015)
Toxoplasmosis, caused by the obligate intracellular protozoan Toxoplasma gondii, is an important zoonosis with medical and veterinary importance worldwide. The disease is mainly contracted by ingesting undercooked or raw meat containing viable tissue cysts, or by ingesting food or water contaminated with oocysts. The diagnosis and genetic characterization of T. gondii infection is crucial for the surveillance, prevention and control of toxoplasmosis. Traditional approaches for the diagnosis of toxoplasmosis include etiological, immunological and imaging techniques. Diagnosis of toxoplasmosis has been improved by the emergence of molecular technologies to amplify parasite nucleic acids. Among these, polymerase chain reaction (PCR)-based molecular techniques have been useful for the genetic characterization of T. gondii. Serotyping methods based on polymorphic polypeptides have the potential to become the choice for typing T. gondii in humans and animals. In this review, we summarize conventional non-DNA-based diagnostic methods, and the DNA-based molecular techniques for the diagnosis and genetic characterization of T. gondii. These techniques have provided foundations for further development of more effective and accurate detection of T. gondii infection. These advances will contribute to an improved understanding of the epidemiology, prevention and control of toxoplasmosis.